Flights-to-quality from EM Bonds to safe-haven US Treasury Securities: A time-frequency Analysis. Issue 2 (26th January 2023) - Gubareva, Mariya; Umar, Zaghum; Teplova, Tamara; Vo, Xuan Vinh
ABSTRACT: We study 2001–2020 flight-to-quality episodes encompassing two planetary-scale crises: the Global Financial Crisis (GFC) of 2007–2008 and the coronavirus-triggered global meltdown. We focus on time-frequency lead-lag nexuses between holding emerging market (EM) debt and investing in relatively risk-free US Treasuries. Wavelet coherency along with the phase-difference approach is used. Our results reveal varying lead-lag patterns and low-coherence zones between EM bonds and US Treasuries, which imply the existence of appealing diversification attributes. The flights-to-quality during the crisis periods, such as the GFC and COVID-19 pandemic, emphasize the safe-haven characteristics of US Treasures. They also evidence that the post-Covid tightening of credit spreads to the pre-crisis levels is faster than the post-GFC recovery. We demonstrate that for EM debt investors, the US Treasury market allows for dynamic risk mitigation strategies during both global crises.